DETOXIFYING PRE-TREATED LIGNOCELLULOSE-CONTAINING MATERIALS - SOONG, CHEE-LEONG; HOLMES, JASON W; DEINHAMMER, RANDY (2008)
The invention relates to a process of detoxifying pre-treated lignocellulose-containing material by subjecting pre-treated material to a detoxifying compound capable of binding 1) pre-treated lignocellulose degradation products and/or 2) acetic acid. The detoxifying compound may also be an amidase and/or and anhydrase. The invention also relates to a process of producing a fermentation product including a detoxification process of the invention. L'invention concerne un procédé de détoxification d'un matériau prétraité contenant de la lignocellulose, consistant à soumettre un matériau prétraité à un composé de détoxification pouvant fixer 1) des produits de dégradation de lignocellulose prétraités et/ou 2) de l'acide acétique. Le composé de détoxification peut également être une amidase et/ou une anhydrase. L'invention concerne également un procédé de production d'un produit de fermentation associé au procédé de détoxification de l'invention.